MISTAKES AND ERROR ANALYSIS OF COHESIVE FEATURES IN ARGUMENTATIVE ESSAY OF FIFTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF JAMBI UNIVERSITY - Hidayati, . (LearnING Journal, 2014)
The aim of this research isÂ  to describe the types of lexical and grammatical mistakes and errors that were committed by students in argumentative essay. In conducting this research, the researcher used descriptive research. There were twenty students as the subject of this research. To collect the data, the researcher conducted three tests in which the students were asked to write three argumentative essays. In analyzing data, the researcher applied some theories that are relevant to this research. These theories are theory of cohesive features, theory of error analysis, and theory of writing. From the result of the test, the researcher found that there were four types of errors namely misformation in using antonym, misformation in using personal pronoun and misformation in using possessive pronoun and omission of additional connective or conjunction. Meanwhile, the researcher found nine types of mistakes namely misformation Â in using personal pronoun, misformation in using possessive pronoun, misformation in using demonstrative reference, misformation in using additional conjunction, misformation in using cause effect conjunction, omission of additional conjunction, omission opposite conjunction, omission of cause effect conjunction, misformation in using noun substitution